SNARE Molecules in Marchantia polymorpha: Unique and Conserved Features of the Membrane Fusion Machinery. (27th May 2015) - Kanazawa, Takehiko; Era, Atsuko; Minamino, Naoki; Shikano, Yu; Fujimoto, Masaru; Uemura, Tomohiro; Nishihama, Ryuichi; Yamato, Katsuyuki T.; Ishizaki, Kimitsune; Nishiyama, Tomoaki; Kohchi, Takayuki; Nakano, Akihiko; et al.
Abstract : The membrane trafficking pathway has been diversified in a specific way for each eukaryotic lineage, probably to fulfill specific functions in the organisms. In green plants, comparative genomics has supported the possibility that terrestrialization and/or multicellularization could be associated with the elaboration and diversification of membrane trafficking pathways, which have been accomplished by an expansion of the numbers of genes required for machinery components of membrane trafficking, including soluble N -ethylmaleimide-sensitive factor attachment protein receptor (SNARE) proteins. However, information regarding membrane trafficking pathways in basal land plant lineages remains limited. In the present study, we conducted extensive analyses of SNARE molecules, which mediate membrane fusion between target membranes and transport vesicles or donor organelles, in the liverwort, Marchantia polymorpha . The M. polymorpha genome contained at least 34 genes for 36 SNARE proteins, comprising fundamental sets of SNARE proteins that are shared among land plant lineages with low degrees of redundancy. We examined the subcellular distribution of a major portion of these SNARE proteins by expressing Citrine-tagged SNARE proteins in M. polymorpha, and the results showed that some of the SNARE proteins were targeted to different compartments from their orthologous products in Arabidopsis thaliana . For example, MpSYP12B was localized to the surface of the oil body, which is a unique organelle in liverworts. Furthermore, we identified three VAMP72 members with distinctive structural characteristics, whose N-terminal extensions contain consensus sequences for N -myristoylation. These results suggest that M . polymorpha has acquired unique membrane trafficking pathways associated with newly acquired machinery components during evolution.